The Creation and Transformation of Regional Parliamentary Assemblies: Lessons from the Pan-African Parliament - (:unkn) unknown (My University, 2010)
This article analyses the genesis and recent evolution of the Pan-African Parliament (PAP), one of the key institutions of African integration. Based on theories relating to the European Parliament, it argues that the dynamics surrounding the establishment of the PAP result from a blend of internal and external factors. On the one hand, the decision to create a PAP can be traced back to the problems of the Organisation of African Unity and to the will of African leaders to revive Pan-Africanism. On the other hand, the establishment and design of the PAP are partially inspired by international precedents such as the European Parliament. Over and above this observation, which is informed by the theory of mimetic institutionalism, the existence of regular interactions between Europe and Africa and, more generally, the outward activities of the PAP, would seem propitious to the self-assertion of this institution. Ultimately, the objective of the article is to lay the ground for a more ambitious theory of regional parliamentary assemblies.
Keywords: African Research